International Counseling Students’ Practicum Experience in a Counseling Program in the United States: A Phenomenological Study - Xiong, Yiying; Bonner , Matthew; Travis, Sterling; Xing, Feng; Zhang, Qingyun (Journal of International Students, 2021)
Limited attention has been given to international counseling students (ICSs) enrolled in U.S. counseling programs. This phenomenological study examined the lived experiences of six ICSs in a U.S. counseling program regarding factors that impacted their practicum experience. The study identified three themes: learning and growth process, positive impacting factors, and negative impacting factors. It also provided stakeholder recommendations